From Historical Identity to Modern Representation: The Evolving Political Role of the Polish Minority in Lithuania – An Overview - Žemaitytė, Aistė (Polonia Inter Gentes, 2025)
This research examines the political influence of the Polish ethnic minority in Lithuania, analyzing its historical foundations, contemporary representation mechanisms, and future integration prospects. Despite constituting only 6.5% of Lithuania’s population, the Polish minority maintains political presence, particularly in southeastern regions such as Vilnius and Šalčininkai districts. The study employs qualitative content analysis of official documents and institutional formation from 2021–2025, focusing on three key dimensions: historical identity formation, political representation and institutional participation, and future integration visions. The analysis reveals that the the Lithuanian Polish Election Campaigns – Unions of Christian Families party (EAPL) has served as the primary vehicle for Polish political mobilization since 1994, achieving consistent success in municipal elections (securing 56–67 mandates) and maintaining representation in national parliament and European Parliament. However, recent developments indicate an evolving pattern of political integration, with Polish-origin politicians increasingly participating in mainstream parties beyond ethnic-based platforms, exemplified by appointments such as Robert Duchnevič as mayor and Ewelina Dobrowolska as former Minister of Justice.The adoption of the National Minorities Law in November 2024 addresses a 14-year legislative vacuum, providing formal recognition and enhanced protections for minority rights. The research concludes that the Polish minority represents a relatively successful case of minority political integration in the Baltic region, though future challenges persist regarding language policy, cultural preservation, and balancing ethnic identity with broader civic participation. The study demonstrates that political mobilization in nationalizing states relies increasingly on symbolic representation rather than substantive policy delivery, while successful integration depends on maintaining cultural vitality alongside active engagement in Lithuania’s pluralistic democratic processes